Medication adherence, treatment satisfaction, and patient–doctor relationship in patients with mood disorders at a Saudi tertiary care hospital: a cross-sectional study - Almadani, Ahmad H.; Alghamdi, Ayedh H.; Alkathiri, Mohammed A.; AlBuqami, Fay H.; Alrahmah, Saleh A.; Aljumah, Khalaf A.; Alenazi, Ziyad B.; Albadi, Elaaf A.; Alfarraj, Yara A.; Alkhilaiwi, Noorah E.; Muhnna, Abdullah K.; Aljaffer, Mohammed A. (Frontiers in Psychiatry, 2026)
IntroductionMood disorders are highly prevalent and associated with substantial impairment. This study examines medication adherence (MA), treatment satisfaction (TS), and patient–doctor relationships (PDRs) among adult patients with mood disorders at a Saudi tertiary hospital.MethodsThis cross-sectional study’s tool employed a questionnaire developed by the researchers, along with the Arabic versions of the Medication Adherence Rating Scale, the Treatment Satisfaction Questionnaire for Medication (TSQM), and the Patient–Doctor Relationship Questionnaire (PDRQ).ResultsAmong the 260 participants, 79.2% demonstrated good MA, 34.23% exhibited low TS, and 62.31% reported good PDRs. Good MA was significantly associated with higher global TSQM scores (adjusted odds ratio [AOR] = 1.04; 95% confidence interval [CI]: 1.02–1.06; p < 0.001) and better PDR (p = 0.034). Illness duration was a significant factor associated with MA (AOR = 0.14; 95% CI: 0.02–0.86; p = 0.034 for 1–5 years compared with < 1 year), TS (AOR = 6.07; 95% CI, 1.80–20.48; p = 0.004 for > 10 years compared with < 1 year), and PDR (p = 0.028). Being supported by family and friends “to some extent” was associated with lower TS (AOR = 0.52; 95% CI: 0.30–0.92; p = 0.024) and poorer PDR (AOR = 0.37; 95% CI: 0.19–0.70; p = 0.002) compared with those receiving more support. Education level was significantly associated with TS, specifically for participants with a bachelor’s degree compared with uneducated participants (AOR = 5.04; 95% CI: 1.73–14.66; p = 0.003). MA was significantly related to age (AOR = 29.83; 95% CI: 1.75–508.3; p = 0.019 for > 65 years old compared with 18–25 years old) and number of regular medications (AOR = 0.66; 95% CI: 0.44–0.99; p = 0.044). A significant relationship was also observed between TS and the perception of having a mental illness and needing treatment (p = 0.001). PDR was significantly better among participants did not have to buy their own psychiatric medication compared with those who always purchased them (AOR = 5.04; 95% CI: 1.81–14.06; p = 0.002) and among those with a history of using alternative methods compared with those without (AOR = 2.23; 95% CI: 1.21–4.11; p = 0.01).ConclusionOur findings highlight the interconnectedness of MA, TS, and PDR, as well as the influence of several factors. Patient-centered specific strategies are needed to address these factors.